Characterization of LPG Hose Quality to Improve Consumer Safety Protection - Mulyono, Ary Budi; Purwanto, Endi Hari (Proceeding International Conference on Religion, Science and Education, 2024)
Standards or technical specifications of a product can guarantee product quality and improve product safety. To guarantee the quality of rubber and thermoplastic hose for LPG stoves circulating in the community, the government has established SNI 7213:2014 Rubber Hoses for LPG Gas Stoves and SNI 8022:2014 Thermoplastic Elastomer Hoses for LPG Gas Stoves. This study aims to identify the characteristics of the LPG hose test results based on SNI 7213:2014 and SNI 8022:2014. The test parameters tested were tensile strength, elongation at break, and aging at 100oC for 72 hours. This study used a quantitative descriptive method and the hose sample was taken using purposive sampling. The results showed that there were still samples of LPG hoses whose test results were close to the maximum/minimum limits of the established SNI quality requirements. This indicates the need for corrective steps to be taken by LPG hose manufacturers so that the LPG hose quality can reach optimal value.